Clinical decision making in frequently encountered anomalous aortic origin of coronary arteries, the impact of IVUS. (14th October 2021) - Verheijen, D B H; Van Der Kley, F; Egorova, A D; Jongbloed, M R M; Kies, P; Hazekamp, M G; Jukema, J W; Vliegen, H W
Abstract: Introduction: The aim in the diagnostic work-up of patients with an anomalous aortic origin of coronary arteries (AAOCA) is to determine whether the course of the coronary artery is benign or malignant. In patients with AAOCA with an interarterial course the guidelines on diagnostics are concise. Recommended CT-scan imaging does not evaluate stress-induced functional consequences like external compression by the pulmonary artery as the scan is performed in a resting state. Non-invasive ischemia detection techniques often lack sufficient sensitivity. To improve functional stratification, exploration of new diagnostic modalities in the diagnostic workup of AAOCA is mandatory. Purpose: The purpose is to explore the potential role of intravascular ultrasound (IVUS) in the diagnostic workup of patients with AAOCA. Methods: Nine patients with an anomalous right coronary artery with an interarterial course were analyzed. A cardiologist evaluated the complaints. Anatomical features of the AAOCA were assessed with CT-scan imaging. Further analyses included ischemia detection and coronary angiography. To assess stress-induced ischemia IVUS and invasive measurements – fractional flow reserve (FFR) and instantaneous wave-free ratio (iFR) – were performed at rest and during adrenaline-induced stress. A slit-like orifice was classified as a width/length (W/L) ratio of ≤0.50, an oval orifice as 0.51–0.9 and a round orifice as >0.91. Results: Potential cardiac complaints were present in seven patients. In 8 (89%) patients CT-images showed an acute angle, in 8 (89%) proximal narrowing and an aortic take-off above the pulmonary valve in 4 (44%). In 7 (78%) patients a slit-like orifice and in two (22%) an oval orifice were observed (table 1). IVUS at rest showed a slit-like orifice in one patient classified as an oval orifice on the CT-images and vice versa in another patient (table 2). The patients classified as an oval orifice with IVUS showed no external compression during adrenaline-induced stress. In 4 (57%) out of 7 patients with an slit-like orifice on IVUS, the width remained unchanged or increased during adrenaline infusion. In 2 patients the width decreased slightly, however, these patients were asymptomatic and no ischemia was detected. In 1 (14%) patient the width remained 1.4mmm and the length increased from 3.2mm to 4.7mm. In this case the vessel ostium was fully engaged with the IVUS catheter, hence, the width could not decrease during adrenaline infusion. This was regarded as external compression. In addition, in this patient ischemia was detected. Conclusion(s): In two (22%) out of 9 patients IVUS gave a better insight of the shape of the orifice than CT. Additionally, the anatomic and functional-dynamic components of compression could be defined with adrenaline-induced stress. Therefore, IVUS can contribute to a better understanding of the functional consequences of the anatomical features and of potential stress-induced external compression. FUNDunding Acknowledgement: Type of funding sources: None.